Динаміка росту та каталазної активності штамів Flammulina velutipes (Curt.: Fr.) Sing. з дендрарію Донецького ботанічного саду НАН України - Федотов, О.В. (Промышленная ботаника, 2003)
Growth and catalase activity (CA) of Flammulina velutipes (Curt.: Fr.) strains in the time of cultivation were studied. Catalase activity of the cultural filtrates was not marked; the highest data of the mycelium CA was observed on the 15–25-th day of cultivation.